UPAYA PENINGKATAN PEMASARAN DAN PELAYANAN TERKAIT APLIKASI PLN MOBILE DI PLN ULP BOJONEGORO KOTA - Putri, Melinda Wahyuning; Samsudin, Acep (Jurnal Bisnis Indonesia, 2024)
The application of technology has a major influence on improving business processesand services in a company, such as the innovation of the PLN Mobile application by PT PLN(Persero). However, the use of PLN Mobile is inseparable from various obstacles, the mostimportant factor is the state of society in matters of technological development. The purposeof this promotion, customer service, and socialization activity is to educate and provideunderstanding to the public about customer service through PLN Mobile. The results obtainedare providing real benefits for customers and the surrounding community in increasing theirunderstanding of PLN ULP services and the use of the PLN Mobile application as analternative solution in meeting their needs.Keywords: PLN Mobile, SocialMedia, Promotion, Customer Service, Socialization.